Ideology and Class Division in Veronica Roth’s Divergent - Wardana, Muhammad Kiki; Roy, Sumita (Talenta Publisher, 2019)
The paper attempts to overview the ideology and the class division amongst factions in the novel. The ideology of the five factions in the future city of Chicago is embedded with self traits which dictates that everyone must fit into one dominant trait. The classification by traits or personalities makes clear provision that society will run as it is expected by the leader of the faction. The Divergent of Veronica Roth postulates the depiction of the utopia society that turns Dystopia by the insurgent led by Tris a character that possesses all the qualities and traits of the faction. The culture and the ideology of bourgeois and slave’s society prevail vividly in the novel which is indicated by the ruling faction, Erudite as the bourgeois while the subjugated faction, Abnegation as the slave society. This paper utilizes the descriptive approach to meticulously break down the events by selecting and highlighting the occurrences in the novel as the way of obtaining the data. The theory of ideology by Raymond Williams (1977) was used in this paper to expose the core or base of cultural ideology amongst the classes. The paper finds out that the every faction has its own ideologies even though they were rooted from the same founding fathers.